2012
DOI: 10.3233/wor-2012-0359-1606
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the thermal comfort model in an environment of metal mechanical branch

Abstract: This study aim s to identify the correlation between the Predicted Mean Vote (PMV) with the therm al sensation (S) of 55 em ployees, establishing a linear multiple regression equation. The m easurement of environm ental variables followed established standards. The survey was conducted in a metal industry located in Ponta Grossa of the State of Parana in Brazil. It was applied the physical model of thermal comfort to the environmental variables and also to the subjective data on the thermal sensations of emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The human body maintains its temperature at approximately 37 • C through several types of heat transfer, like sweat and vascular expansion [34][35][36], seeking to keep itself in a thermally comfortable situation in relation to its environment [37]. During the execution of exercises, the blood flow to the muscles used undergoes vasoconstriction and it is observed that there is an increase in skin temperature in the muscle region used during the activity performed [38,39] and that will remain during the execution of the exercise; there is also a vasodilatory response in order to facilitate heat loss through the skin, which will lead to a reduction in body temperature [34,35,39] in order to keep body temperature within acceptable limits.…”
Section: Introductionmentioning
confidence: 99%
“…The human body maintains its temperature at approximately 37 • C through several types of heat transfer, like sweat and vascular expansion [34][35][36], seeking to keep itself in a thermally comfortable situation in relation to its environment [37]. During the execution of exercises, the blood flow to the muscles used undergoes vasoconstriction and it is observed that there is an increase in skin temperature in the muscle region used during the activity performed [38,39] and that will remain during the execution of the exercise; there is also a vasodilatory response in order to facilitate heat loss through the skin, which will lead to a reduction in body temperature [34,35,39] in order to keep body temperature within acceptable limits.…”
Section: Introductionmentioning
confidence: 99%